PERAMBATAN RETAK (CRACK PROPAGATION) TAP BOLT UNC - OIL COATED ASTM 325 - Putra, Trisna (Jurnal Teknik Mesin (JTM), 2012)
Have done a series of studies of crack propagation that trigger the failure of a component machine tap bolts of ASTM 325 standard type as the completeness of the machine elements. From the data analysis carried out showed that the initial microscopic crack starting line with the outer screw rotation groove tightening screw on the event. Triggers visible failure of the voltage degradation around where the defect on the outer as the main trigger. Furthermore, it can be concluded that the manufacturing process and the lack homogenan bolt material becomes the main character of failure.